THE INFLUENCE OF SOCIAL ENVIRONMENT AND TEEN ATTITUDESTOWARD CHANGE VALUES IN THE VILLAGE OF CUPAK KABUPATEN SOLOK - Riki Wanda Putra (Jurnal Ilmu Pendidikan Ahlussunnah, 2018)
This study aims to collect, process, analyze and describe and discuss about: knowing theinfluence of the social environment and teen attitudes towards changes in the value of thesystem in the Nagari Cupak in Kabupaten Solok. The type of research used in this studyis quantitative descriptive research. To achieve the research objectives the data collectiontechnique uses a questionnaire. Processing data to test reliability using the ProductMoment formula, which is then continued by Sperman Brown. The formula data analysistechnique uses a percentage of determination. The results showed that there was asignificant influence between teen attitudes toward changing values in Nagari Cupak,because the teenage social environment of Nagari Cupak had an important role as avehicle that was non-formal in creating or forming teen character or attitude in NagariCupak in socializing and socializing and communicate in Nagari Cupak Kabupaten Solok